Identification Of Bacteria Causing Nosocomial Infections In Patients In The Care Ward At Kendari City General Hospital In 2023 - Sufiah Asri Mulyawati; Laode Kardin; Nina Indriyani Nasruddin; Edy Husnul Mujahid; Tsalsa Anto Ifdanunnisa (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2025)
ABSTRACT Background: Bacteria are microorganisms that have a single cell, prokaryotes. Normal skin is usually occupied by bacteria around 102-106 CFU/ml. Purpose(s): This study aims to determine the characteristics of the bacteria from hand swabs in ward patients at the Kendari City Regional General Hospital in 2023. Methods: This research is an observational descriptive study. The research sample was taken from the patients in patient room. The samples obtained were then cultured at the Microbiology Laboratory, Faculty of Medicine, Halu Oleo University. Analyzed descriptively and displayed in tabular form. Results: The results showed that there was growth of bacterial colonies. The bacteria found in the samples from the patient's hand swabs were Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus sp., Bacillus sp., Enterobacter sp. Conclusion: There was growth of bacterial colonies obtained from the results of hand swabs of ward care patients at the Kendari City Regional General Hospital.